2004
DOI: 10.1055/s-2004-832695
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Pathophysiology of Diverticular Disease

Abstract: Diverticular disease is prevalent in Western countries and yet its pathogenesis remains poorly understood. The common theories of the cause of diverticular disease have focused on colonic motility, the structural aspects of the colonic wall, and the role of dietary factors, particularly fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 46 publications
0
28
1
13
Order By: Relevance
“…18 Approximately 10 to 25% of patients with diverticulosis will develop diverticulitis. 19,20 The prevalence of the disease in men is approximately equal to that of women. McConnell et al reported that diverticular bleeding occurs more commonly in men and strictures and obstructions occur more often in women.…”
Section: Epidemiologymentioning
confidence: 99%
“…18 Approximately 10 to 25% of patients with diverticulosis will develop diverticulitis. 19,20 The prevalence of the disease in men is approximately equal to that of women. McConnell et al reported that diverticular bleeding occurs more commonly in men and strictures and obstructions occur more often in women.…”
Section: Epidemiologymentioning
confidence: 99%
“…The pathogenesis of colonic diverticula is complex and multifaceted. Three major contributing factors have been described, namely disordered intestinal motility, deficiencies of dietary fibre and structural abnormalities of the intestinal wall . These factors cause areas of weakness to form where the vasa recta penetrates the muscularis propria.…”
Section: Discussionmentioning
confidence: 94%
“…It can be found in over 40% of the population over 60 years of age compared with only 2% of the population under 30 [1]. Although the whole colon can be aff ected, there is a tendency for diverticulosis to occur on the left side, particularly in the sigmoid colon [1]. In the vast majority of cases, the disease remains asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic diverticulosis is a very common condition in Western societies and has an increased prevalence with age. It can be found in over 40% of the population over 60 years of age compared with only 2% of the population under 30 [1]. Although the whole colon can be aff ected, there is a tendency for diverticulosis to occur on the left side, particularly in the sigmoid colon [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation